A sociohydrological model for evaluating the drought resilience of indigenous and modern dryland irrigation systems in Sri Lanka - Wickramasinghe, Romitha; Nakamura, Shinichiro (Frontiers in Environmental Science, 2025)
Over the millennia, indigenous small tanks (small reservoirs or ponds) have served to store rainwater and surface runoff to irrigate drylands. However, despite their significance, small tanks have been gradually abandoned in drylands over the past decades to expand cultivable areas under modern agricultural interventions, such as dam reservoirs and canal systems. Sole reliance on modern water interventions has intensified freshwater stress and rendered dryland agriculture vulnerable to droughts. Herein, we present a sociohydrological model incorporating the concept of human salience (i.e., attention accorded by farmers based on actual and perceived reservoir water availability and rainfall) and access to small tanks to simulate farmer decisions on cultivation area. By applying the model to a centrally managed modern irrigation system and a quasi-decentralized indigenous irrigation system in the Mahaweli H irrigation scheme of the Sri Lankan dry zone for the 2010–2020 period, we calibrated farmer perception levels to show that indigenous system farmers perceive a significantly low rainfall threshold indicating greater adaptability to dry conditions. Sensitivity of perception levels to cultivation area demonstrate that modern system farmers have an 18% higher dependency on reservoir water availability compared to indigenous farmers when deciding cultivation area. This stark dependency on reservoir water availability of modern system farmers is rooted in lack of accessibility to small tanks, a feature that enhance drought resilience of farmers in the indigenous system. While providing quantifiable insights, this comparative assessment underscores the importance of critically evaluating the efficacy of decentralized indigenous small tanks in current water resource investments.